(untitled) (Research, Society and Development, 2023)
The correct business management is essential for the survival of companies, especially in the Industry 4.0 scenario, where changes are increasingly rapid and complex, increasing market competitiveness. The case study objective was to evaluate a family radiator repair company located in Volta Redonda-RJ, in four dimensions: operational, financial, commercial, and quality, seeking to propose improvements without burden or at low cost for the owner, considering its operating capacity. current. Furthermore, tools were implemented to assist in the company’s day-to-day management, optimizing the organization of relevant data and aiming to create relevant parameters and goals for analyzing the quality of the service provided. For these objectives, quality tools were used, such as KPI (Key Performance Indicator), bibliographies, such as Motta, Lobato, and Pereira, and sources from IBGE, SEBRAE, and previous academic publications. Considering all the points presented, it was concluded that there were several points to improve, and those with the greatest impact on the company’s growth and operability were prioritized for applying tools and suggesting management methods.